Histidine‐Tryptophan‐Ketoglutarate Solution With Added Ebselen Augments Myocardial Protection in Neonatal Porcine Hearts Undergoing Ischemia/Reperfusion. Issue 2 (16th December 2014) - Chen, Yan; Liu, Jinping; Li, Shoujun; Yan, Fuxia; Xue, Qinghua; Wang, Huiying; Sun, Peng; Long, Cun
Abstract Whether modified histidine‐tryptophan‐ketoglutarate (HTK) solution offers myocardial protection to newborn heart has not been documented. The purpose of this study was to compare myocardial protection using HTK added by ebselen with HTK in a piglet model of cardiopulmonary bypass (CPB). Fifteen piglets were randomly assigned to three groups: the control group (C group, n = 5), HTK solution group (HTK group, n = 5), and HTK added by 10 nM ebselen group (HTK+E group, n = 5). Animals in the two experimental groups were placed on hypothermic CPB, after which the ascending aorta had been clamped for 2 h. The control animals underwent normothermic CPB without cardiac arrest. Myocardial antioxidant activities, myocytes apoptosis and mitochondrial structures, as well as the release of cytochrome c and the expression of Bax, Bcl‐2, and HSP72 protein in myocardium were measured. Increased myocardial superoxide dismutase (SOD) and Mn‐SOD activities, decreased TUNEL‐positive cells, and reduced release of cytochrome c were noted in the HTK+E group compared with those in the HTK group (P = 0.021, P = 0.020, P = 0.045, and P = 0.010, respectively). The Bax/Bcl‐2 ratio in the HTK group was significantly higher than that in the C group (P = 0.024). The expression of HSP72 protein and mRNA in the HTK+E group was higher than that in the HTK group (P = 0.039 and P = 0.035, respectively). Mitochondrial score under electron microscope in the HTK+E group was lower than that in the HTK group (P = 0.047). Improved antioxidant defense, reduced myocytes apoptosis, and better preserved mitochondrial structure were observed in the HTK+E group. Ebselen added to HTK provides better myocardioprotection to HTK solution for the neonatal heart.